Pengolahan Air Sumur Menggunakan Limbah Cangkang Telur Ayam Sebagai Biokoagulan Dalam Penurunan Logam Besi (Fe) dan Kekeruhan - Frisilla, Maria Casandra; Pramadita, Suci; Nugraheni, Putranty Widha (Universitas Tanjungpura, 2026)
Clean water is essential for human life; however, its distribution in Kubu Raya Regency remains limited, prompting residents to rely on dug wells as their primary water source. In the Hosana Fhileo residential area, groundwater quality exceeds permissible limits, with iron (Fe) concentration at 14.41 mg/L and turbidity at 288 NTU, surpassing the standards set by the Indonesian Ministry of Health Regulation No. 2 of 2023. Concurrently, the abundance of eggshell waste offers potential for its use as a natural coagulant due to its calcium carbonate (CaCO₃) content. This study aims to evaluate the effectiveness of eggshell powder as a coagulant in reducing iron concentration and turbidity in groundwater, and to compare it with the chemical coagulant Poly Aluminium Chloride (PAC). Laboratory-scale jar tests were conducted in two stages: the first used eggshell powder at 30, 50, and 70 g/L, while the second used PAC at 60, 70, and 80 g/L. Results showed that a 70 g/L dose of eggshell powder reduced iron concentration by 34.52% to 9.44 mg/L (p = 0.003 < 0.05) and turbidity by 90.61% to 27.05 NTU (p = 0.002 < 0.05). In contrast, a 60 g/L PAC dose increased iron levels to 16.32 mg/L (p = 0.002 < 0.05), but reduced turbidity by 84.57% to 44.43 NTU (p = 0.001 < 0.05). These findings indicate that eggshell powder is a promising eco- friendly coagulant. However, its Fe removal efficiency may be improved through process optimization, such as pH adjustment to enhance coagulation performance.